Unconventional Actions of Glycoprotein Hormone Subunits: A Comprehensive Review - Querat, Bruno (Frontiers in Endocrinology, 2021)
The glycoprotein hormones (GPH) are heterodimers composed of a common α subunit and a specific β subunit. They act by activating specific leucine-rich repeat G protein-coupled receptors. However, individual subunits have been shown to elicit responses in cells devoid of the receptor for the dimeric hormones. The α subunit is involved in prolactin production from different tissues. The human chorionic gonadotropin β subunit (βhCG) plays determinant roles in placentation and in several cancer development and metastasis. A truncated form of the thyrotropin (TSH) β subunit is also reported to have biological effects. The GPH α- and β subunits are derived from precursor genes (gpa and gpb, respectively), which are expressed in most invertebrate species and are still represented in vertebrates as GPH subunit paralogs (gpa2 and gpb5, respectively). No specific receptor has been found for the vertebrate GPA2 and GPB5 even if their heterodimeric form is able to activate the TSH receptor in mammals. Interestingly, GPA and GPB are phylogenetically and structurally related to cysteine-knot growth factors (CKGF) and particularly to a group of antagonists that act independently on any receptor. This review article summarizes the observed actions of individual GPH subunits and presents the current hypotheses of how these actions might be induced. New approaches are also proposed in light of the evolutionary relatedness with antagonists of the CKGF family of proteins.